2005
DOI: 10.1177/0310057x0503300106
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adjunctive Fresh Frozen Plasma Administration on Coagulation Parameters and Survival in a Canine Model of Antivenom-treated Brown Snake Envenoming

Abstract: This study aimed to assess the effects of dugite envenoming on blood coagulation and platelet count in a canine model, and the efficacy of fresh frozen plasma (FFP) in reversing the clotting disorder after both adequate and inadequate venom neutralization. Following initial dosing and administration studies, an intravenous venom dose of 1μg/kg was administered to eleven dogs. This was followed 30 minutes later by antivenom in either adequate or inadequate doses. A further 30 minutes later, the animals were giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…The administration of FFP in crotalid envenomation victims is controversial. Clinicians must consider both the need to replenish clotting factors lost to consumption and the concern that the additional clotting factors may result in acceleration of fibrinolysis and exacerbate hemorrhage until all venom is neutralized . A study evaluating the efficacy of FFP to reverse venom‐induced coagulopathy in dogs envenomated with brown snake venom showed that most dogs receiving plasma were afibrinogenemic and death only occurred in dogs that received plasma .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The administration of FFP in crotalid envenomation victims is controversial. Clinicians must consider both the need to replenish clotting factors lost to consumption and the concern that the additional clotting factors may result in acceleration of fibrinolysis and exacerbate hemorrhage until all venom is neutralized . A study evaluating the efficacy of FFP to reverse venom‐induced coagulopathy in dogs envenomated with brown snake venom showed that most dogs receiving plasma were afibrinogenemic and death only occurred in dogs that received plasma .…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians must consider both the need to replenish clotting factors lost to consumption and the concern that the additional clotting factors may result in acceleration of fibrinolysis and exacerbate hemorrhage until all venom is neutralized . A study evaluating the efficacy of FFP to reverse venom‐induced coagulopathy in dogs envenomated with brown snake venom showed that most dogs receiving plasma were afibrinogenemic and death only occurred in dogs that received plasma . Alternatively, a retrospective study in human medicine showed early FFP administration was associated with earlier improvement of coagulation function within 4 hours and was not associated with hemorrhage or death .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an effect can accelerate fibrinolysis, which will enhance further bleeding through the release of fibrin degradation products . One canine study from Australia assessed FFP and antivenom in dogs with brown snake (genus Pseudonaja , family Elapidae ) envenomation . Persistent afibrinogenemia was present in both study groups, one having received antivenom only and the other receiving antivenom and FFP .…”
Section: Treatmentmentioning
confidence: 99%
“…One canine study from Australia assessed FFP and antivenom in dogs with brown snake (genus Pseudonaja , family Elapidae ) envenomation . Persistent afibrinogenemia was present in both study groups, one having received antivenom only and the other receiving antivenom and FFP . Heparin should never be used because it is ineffective for treating the venom‐induced coagulopathy and because of its potentiating effect on antithrombin .…”
Section: Treatmentmentioning
confidence: 99%